ASSESSMENT OF THE EFFECTIVENESS OF AN INNOVATIVE JUDICIAL TRAINING PROGRAM AT THE INITIAL STAGE OF TRAINING - Abadan Ismailova (Web of Journals Publishing, 2024)
The traditional technology of training arbitrators at the initial stage of training is determined by the principles of contextual learning, through saturation with elements of professional activity. Such a system has a number of disadvantages in contrast to the competence-based approach to teaching. The article substantiates the effectiveness of the developed training program based on a competency-based approach based on the dynamics of theoretical and technical preparedness, as well as the results of sports activities.
Keywords: football referees, initial training, professional activity, competence-based approach.